Evidence based survey of the distribution volume of ethanol: Comparison of empirically determined values with anthropometric measures. (January 2019) - Maskell, Peter D.; Jones, A. Wayne; Savage, Anne; Scott-Ham, Michael
Highlights: Blood-alcohol calculations are often required in forensic science casework and commonly involve the Widmark equation. Anthropometric equations can tailor Widmark's rho-factor for a given individual. Results using anthropometric equations were in reasonably good agreement with rho-factors determined empirically. A regression equation involving the person's age, height and body weight was the best model for male subjects. Consideration of the person's BMI gave more accurate results for females. Abstract: The Widmark equation is commonly used when blood alcohol calculations are required in forensic and legal medicine, such as in road-traffic cases and alcohol-related deaths. An important biological variable in this connection is the volume of distribution (Vd ) of ethanol, which is commonly referred to as the rho-factor. Although a person's Vd can be determined empirically through controlled drinking experiments, this approach is not very practical in reality. For this reason, a number of anthropometric equations have been developed that utilize sex, age, height and weight to estimate the person's total body water (TBW) and hence Vd of ethanol. To date, there are not any studies that compare Vd derived from anthropometric data with robust values measured empirically. From the literature we compiled information about the Vd of ethanol from drinking studies with 173 Caucasian males and 63 Caucasian females from Western Europe. These empirically derived values of Vd were then compared with estimates derived from various anthropometric equations. In males the Watson, Watson and Batt regression equation involving age, height and weight gave the most accurate results (bias was 0.00 L/kg) and 95% range ±0.13 L/kg. The equation derived by Forrest, which took into consideration a person's body mass index (BMI), gave the best estimates of Vd for females; mean bias −0.01 L/kg and range ±0.15 L/kg.